Effect of Liquidity and Company Size on Company Value of Food and Beverage Companies Listed in The Indonesia Effects Secretary for The Period 2018-2022 - Yulia Elsa Kartika (Green Publisher, 2024)
The phenomenon occurring in Food and Beverage (F&B) companies listed on the Indonesian Stock Exchange (IDX) reflects the broader development of the F&B industry in Indonesia. This research aims to provide an overview of the condition of the F&B industry in Indonesia by examining the impact of liquidity and company size on firm value. This quantitative and associative study utilizes non-participant observation to collect data from the official IDX website (www.idx.co.id) and relevant company websites, focusing on financial reports for analysis. The population consists of F&B companies listed on the IDX from 2018 to 2022. Using purposive sampling, 29 companies were selected, resulting in a total of 145 observations over five years. Data analysis was conducted using the E-Views application. The results indicate that both liquidity and company size have a positive and significant effect on firm value. Recommendations for company management include optimizing inventory to ensure smooth operations and minimizing storage costs. Investors are advised to consider liquidity ratios, such as the current ratio and quick ratio, to assess a company's ability to meet short-term obligations. Future research should incorporate additional variables such as leverage, capital structure, and governance, employing both qualitative and quantitative approaches to gain a deeper understanding of these relationships. Comparing results across different contexts can also enhance understanding.